A Different Approach: The Role of Oxygen Isotope Polarity and Coupling Dynamics in Enhancing Sub-Barrier Fusion - S. Abdalmajid, Lina; M. Saeed, Adil M. Hussein (Iraqi Journal of Physics, 2025)
This study investigates the influence of projectile deformation and coupled-channel dynamics, including neutron transfer, multipole vibrations, and multi-phonon excitations, on the fusion cross-sections of oxygen-induced reactions. Fusion excitation functions and barrier distributions are systematically calculated for systems O16,18 + Ni62, Sn116 and Pb208. For theoretical calculations, Wong’s formula and a modified version of the CCFULL code, incorporating the BW 91 and AW 95 proximity potentials, are used. Sub-barrier fusion enhancement, multi-phonon excitation effects, and neutron transfer channel influences are investigated by benchmarking theoretical predictions against experimental data. The agreement between calculated and experimental fusion cross sections is greatly improved, especially using the BW91 potential, by the inclusion of inelastic excitations and neutron transfer reactions with negative Q-values. Barrier distribution analysis shows the crucial role of nuclear structure in determining the fusion probability landscape and serves as a benchmarking technique for assessing theoretical calculations. Modified CCFULL code integrated with BW91 and AW95 potentials enhanced the O16,18 + Sn116, Pb208 systems. The O18 + Sn116 reaction resulted in a calculated cross-section value that doubled when compared to the O16 + Sn116 system. A similar rate was observed for the O18 projectile, leading to a coupled energy width of the barrier distribution in relation to the findings from the O16 projectile. Additionally, for the O18 + Pb208 system, the barrier distribution determined by the three-point method agreed well with the experimental peak.